Compiling the wisdom of Kerala's indigenous farmers: A traditional rice pest management calendar - S K Sreejina; M Nasser
This study documents traditional pest management practices among rice farmers in Kerala, emphasizing low-cost, ecologically grounded methods rooted in indigenous knowledge. Field surveys and interviews identified techniques including manual removal, sweeping with tools or aromatic plants, cultural practices (e.g., flooding, drainage), light traps, botanical and organic deterrents, cow dung slurry for seed treatment, and bioproducts like jeevamrutham and panchagavya. Vertebrate pests were managed using physical barriers, sound deterrents, and natural repellents. A seasonal pest management calendar was developed from these observations. The findings indicate that traditional practices can effectively reduce pest incidence and enhance plant health, though further scientific validation is needed for integration into formal Integrated Pest Management (IPM) frameworks.